Preparation method of modified silica sol and application of modified silica sol in water-based UV coating

By bonding silane coupling agent on the silica sol and combining the use of cationic and anion exchange resins, the problem of insufficient bonding between silica sol and silane in the prior art is solved, and the efficient application of modified silica sol in aqueous UV coatings is achieved, and the adhesion and iodine resistance of the coating are improved.

CN119799037AActive Publication Date: 2025-04-11YUNYAN MATERIALS TECH (SHANGHAI) CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510000747.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

In the existing silane-modified silica sol method, the bond between the sol colloid and the silane is insufficient, resulting in poor modification effect and insufficient process stability.

Method used

By mixing the silica sol with the cation exchange resin, adjusting the pH value, and then dropping the aqueous solution of silane coupling agent and inorganic salt to the mixed solution, bonding the silane coupling agent to the surface of the silica sol, and adjusting the pH value of the reaction system through the anion exchange resin, obtaining a silane coupling agent-modified silica sol.

Benefits of technology

The bonding amount of silane on the surface of silica sol particles is improved, the modification effect of modified silica sol is enhanced, the adhesion and iodine resistance of aqueous UV coatings are improved, and the stability of the process is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225003490000031
    Figure BDA0005225003490000031
  • Figure BDA0005225003490000032
    Figure BDA0005225003490000032
  • Figure BDA0005225003490000091
    Figure BDA0005225003490000091
Patent Text Reader

Abstract

The invention discloses a preparation method of modified silica sol and application of the modified silica sol in a water-based UV coating, and the preparation method comprises the following steps: 1) mixing silica sol with cation exchange resin to enable the pH value of the mixed solution to be 1-7; (2) dropwise adding a silane coupling agent and an aqueous solution of inorganic salt into the mixed solution obtained in the step (1), so that the silane coupling agent is bonded to the surface of the silica sol; and (3) adding anion exchange resin into the reaction solution in the step (2) to enable the pH value of the reaction system to be 2-12, and filtering to obtain the silane coupling agent modified silica sol. When the silane coupling agent modified silica sol is used for a water-based UV coating, the adhesive force and iodine resistance of the UV coating on a PVC base material can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing modified silica sol, and more specifically to a method for preparing silica sol modified by a silane coupling agent and application of the silica sol in water-based UV coatings. Background Art

[0002] Silica sol is an inorganic nanomaterial with excellent performance. It is a colloidal solution formed by uniform dispersion of amorphous silica particles in water or organic solvents. It is an inorganic polymer material with extremely wide applications. It has a large number of applications in chemical mechanical polishing (CMP), textile industry, investment casting, ceramics, coatings and papermaking industries. Silica sol has a large number of silanol groups and has a very good affinity for aqueous systems. However, silica sol has poor compatibility with organic polymer monomers. Silica sol with a single composition and structure can no longer meet the application requirements of some special fields. With the help of silane coupling agents to bridge the gap between inorganic and organic materials, silica sol modified with silane coupling agents can just make up for the defects of ordinary silica sol and expand its application range.

[0003] At present, the most commonly used method for silane-modified silica sol in the industry is to add an appropriate amount of silane to the acidic silica sol and stir and hydrolyze it. The main defect of this method is that the amount of silane actually bonded to the sol colloid is relatively small, which does not achieve the purpose of organic modification. The further optimized process is to adjust the pH value of the system and increase the condensation of silane hydrolyzate. This method also has the risk of silane gelation itself and is not stable enough. Summary of the invention

[0004] In one aspect, the present invention provides a method for preparing a modified silica sol, the method comprising the following steps:

[0005] 1) mixing silica sol and cation exchange resin so that the pH of the mixed solution is 1 to 7;

[0006] 2) adding a silane coupling agent and an aqueous solution of an inorganic salt to the mixed solution of step 1) to allow the silane coupling agent to bond to the surface of the silica sol;

[0007] 3) adding anion exchange resin to the reaction solution of step 2) to make the pH value of the reaction system be 2-12, and filtering to obtain silica sol modified by silane coupling agent.

[0008] In another preferred embodiment, the pH of the silica sol is 8-12, and the particle size is 5-100 nm.

[0009] In another preferred embodiment, the solid content of the silica sol is 5-40%.

[0010] In another preferred embodiment, the silane coupling agent is selected from alkoxysilane containing alkyl substituents, alkoxysilane containing unsaturated double bonds, alkoxysilane containing epoxy groups, alkoxysilane containing amino groups, or a combination thereof.

[0011] In another preferred embodiment, the alkoxysilane containing an alkyl substituent is selected from methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, or a combination thereof.

[0012] In another preferred embodiment, the alkoxysilane containing unsaturated double bonds is selected from vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, or a combination thereof.

[0013] In another preferred embodiment, the epoxy-containing alkoxysilane is selected from γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0014] In another preferred embodiment, the amino-containing alkoxysilane is selected from aminopropyltrimethoxysilane, aminopropyltriethoxysilane, or a combination thereof.

[0015] In another preferred embodiment, the cation exchange resin is selected from 3 H) or carboxylic acid group (-COOH) styrene-divinylbenzene copolymer.

[0016] In another preferred embodiment, the inorganic salt is selected from sodium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, or a combination thereof.

[0017] In another preferred embodiment, the anion exchange resin is selected from 3 ) 3 OH] or tertiary ammonium [-N(CH 3 ) 2 ] of styrene-divinylbenzene copolymer.

[0018] In another more preferred embodiment, in step 1), the mass ratio of the cation exchange resin to the silica sol is 0.1 to 0.9:1, more preferably 0.3 to 0.8:1.

[0019] In another more preferred embodiment, step 1) is stirred at 40-70° C. for 0.5-2 h, more preferably at 45-60° C. for 0.5-1.5 h.

[0020] In another more preferred embodiment, in step 2), the mass ratio of the silane coupling agent to the silica sol is 0.008 to 0.1:1, more preferably 0.01 to 0.08:1.

[0021] In another more preferred embodiment, in step 2), the mass ratio of the inorganic salt to the silica sol is 0.0001 to 0.01:1, more preferably 0.0005 to 0.08:1.

[0022] In another more preferred embodiment, step 2) is continued stirring at 35-65°C for 4-7 hours, more preferably, continued stirring at 45-60°C for 5-6 hours.

[0023] In another more preferred embodiment, in step 2), the stirring rate is 10 to 200 rpm.

[0024] In another more preferred embodiment, in step 3), the mass ratio of the anion exchange resin to the silica sol is 0.1 to 0.6:1, more preferably 0.1 to 0.4:1.

[0025] In another more preferred embodiment, in step 3), the temperature is 10-40° C. for 4-7 hours.

[0026] Another aspect of the present invention provides the use of the silica sol obtained by the above preparation method in the preparation of water-based UV coatings, wherein the UV coatings are used for roller coating on PVC substrates.

[0027] Another aspect of the present invention provides a water-based UV coating, which contains the silica sol obtained by the above preparation method.

[0028] In another more preferred embodiment, the raw materials for preparing the water-based UV coating include the following components in parts by weight:

[0029]

[0030] In another more preferred embodiment, the raw materials for preparing the water-based UV coating include the following components in parts by weight:

[0031]

[0032]

[0033] The present invention also provides a method for preparing the above-mentioned water-based UV coating, the preparation method comprising the following steps:

[0034] (1) Place the water-based UV resin into a dispersion tank and stir with a mixer.

[0035] (2) slowly adding modified silica sol, water, cosolvent, initiator, and wetting agent, and stirring continuously for 20 to 40 minutes to mix evenly;

[0036] (3) Slowly add thickener to adjust the viscosity of the coating according to different coating processes.

[0037] (4) Use a 200-mesh filter bag to filter and complete the preparation of water-based UV coating. DETAILED DESCRIPTION

[0038] After in-depth research, the inventors of this application found that the silicon dioxide in the alkaline silica sol can be converted into the desired functional group silane-modified silica sol at one time through the coordinated action of ion exchange resin and inorganic salt. This technology can be used to customize the functional groups on the surface of the silica sol.

[0039] The preparation method of the modified silica sol provided by the present invention comprises the following steps:

[0040] 1) mixing silica sol and cation exchange resin so that the pH of the mixed solution is 1 to 7;

[0041] 2) adding a silane coupling agent and an aqueous solution of an inorganic salt to the mixed solution of step 1);

[0042] 3) Add anion exchange resin to the reaction solution of step 2), continue stirring at 10-40° C. to make the pH value of the reaction system 2-12, and filter to obtain silica sol modified by silane coupling agent.

[0043] In the preparation method of the modified silica sol of the present invention, the silica sol used is alkaline, and its pH is 8-12. In some specific embodiments, the pH of the silica sol is 8-10, 8-9, 9-10, 10-11, etc. In some specific embodiments, the particle size of the silica sol used is 5-100nm. In some more preferred specific embodiments, the particle size of the silica sol used is 20-30nm, 40-50nm, 50-60nm, 60-80nm, 70-90nm, 80-100nm, etc. In some specific embodiments, the solid content of the silica sol used is 5-40%. In some more preferred specific embodiments, the solid content of the silica sol used is 15-20%, 20-25%, 20-30%, 30-40%, etc.

[0044] In the preparation method of the modified silica sol of the present invention, the role of the cation exchange resin is to exchange the cations in the silica sol and reduce the metal ion content in the system. The cation exchange resin that can be used in the present invention includes but is not limited to cation exchange resins having sulfonic acid groups (-SO 3 H) or carboxylic acid group (-COOH) styrene-divinylbenzene copolymer.

[0045] In the preparation method of the modified silica sol of the present invention, the silane coupling agent is bonded to the surface of the silica sol by hydrolysis and polycondensation, and a special organic group is added to the surface, which changes the morphology of the sol surface mainly composed of hydroxyl groups. The silane coupling agent that can be used in the present invention includes but is not limited to alkoxysilanes containing alkyl substituents (such as methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane), alkoxysilanes containing unsaturated double bonds (such as vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane), alkoxysilanes containing epoxy groups (such as γ-(2,3-epoxypropyloxy)propyltrimethoxysilane), and alkoxysilanes containing amino groups (such as aminopropyltrimethoxysilane and aminopropyltriethoxysilane).

[0046] In the preparation method of the modified silica sol of the present invention, the role of the inorganic salt is to slowly increase the cation content in the reaction system as the reaction progresses, and at the same time to control the speed of bonding between silane and the hydroxyl group on the surface of the silica sol. Compared with the step of directly using a modifier for modification without adding an inorganic salt, in the preparation method of the modified silica sol of the present invention, as the inorganic salt is introduced into the entire reaction system, the pH of the system can be gradually changed from acidic to weakly alkaline as the reaction progresses, while avoiding the defects of silane hydrolyzate being difficult to bond to the surface of the silica sol under acidic conditions and silane hydrolyzate being easy to condense into gel under alkaline conditions. The inorganic salts that can be used in the present invention include but are not limited to sodium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium sulfate, potassium sulfate, magnesium sulfate, and calcium sulfate.

[0047] In the preparation method of the modified silica sol of the present invention, the role of the anion exchange resin is to exchange the anions introduced by the inorganic salt. The anion exchange resin that can be used in the present invention includes but is not limited to a quaternary ammonium group [-N(CH 3 ) 3 OH] or tertiary ammonium [-N(CH 3 ) 2 ] of styrene-divinylbenzene copolymer.

[0048] In step (1) of the method for preparing the modified silica sol of the present invention, the amount of the cation exchange resin is not particularly limited, as long as the pH of the silica sol is adjusted to 1 to 7. More preferably, the mass ratio of the silica sol to the dehydrated cation exchange resin is 1:0.30 to 0.80, for example, 1:0.4, 1:0.5, 1:0.55, 1:0.6, 1:0.7, etc. The reaction temperature is not particularly limited, but is preferably 20-70°C, more preferably 45-60°C, for example, 45°C, 48°C, 50°C, 55°C, 58°C, 60°C, etc.

[0049] In step 2) of the preparation method, the amount of the silane coupling agent is preferably such that the mass ratio of the silane coupling agent to the alkaline silica sol is 0.008 to 0.1:1, more preferably, 0.01 to 0.0.08. For example, 0.01:1, 0.015:1, 0.01:1, 0.27:1, etc. The amount of the inorganic salt is not particularly limited, and more preferably, the mass ratio of the silane coupling agent to the alkaline silica sol is 0.0001 to 0.01:1, more preferably, 0.0005 to 0.08:1, for example, 0.0014:1, 0.0012:1, 0.0014:1, 0.0015:1, 0.002:1, etc. The concentration of the aqueous solution of the inorganic salt is not particularly limited. Preferably, the concentration of the aqueous solution of the inorganic salt is 0.5 to 1.5 mol / L, for example, 1.0 mol / L, 1.2 mol / L, or 1.5 mol / L.

[0050] In step 2), the stirring rate is not particularly limited, preferably, the stirring rate is 10-200 rpm. The reaction temperature is not particularly limited, preferably 30-60° C., more preferably, 35-60° C., for example, 35° C., 45° C., 55° C., etc. The reaction time is not particularly limited, preferably 4-7 hours, more preferably 5-6 hours, for example, 5 hours, 6 hours or 7 hours.

[0051] In step 3), the mass ratio of the anion exchange resin to the silica sol is 0.1 to 0.6:1, preferably 0.1 to 0.4:1. For example, 0.2:1, 0.25:1, 0.3:1, 0.35:1,

[0052] The water-based UV coating of the present invention is an environmentally friendly coating that combines the advantages of traditional UV coatings and water-based coatings. Water is used as a diluent, which greatly reduces the emission of volatile organic compounds (VOCs). Under the irradiation of ultraviolet light, the photoinitiator absorbs the radiation energy of the ultraviolet light and splits into free radicals, which triggers the polymerization and cross-linking grafting reactions of the prepolymer. It can be quickly cured in a short time by ultraviolet irradiation, greatly improving the production efficiency and facilitating continuous production.

[0053] Compared with the prior art, the present invention has the following advantages:

[0054] In the preparation method of the modified silica sol of the present invention, the hydrolysis rate of the silane coupling agent can be controlled due to the addition of the inorganic salt, so that the silane coupling agent will not undergo a gelation reaction during the bonding process with the silica sol.

[0055] After the water-based UV coating prepared by the modified silica sol prepared by the preparation method of the modified silica sol of the present invention is rolled onto a PVC substrate, the adhesion and iodine resistance performance are significantly improved.

[0056] The present invention will be further described below in conjunction with specific examples. Specific examples are implemented under the premise of technical solutions of the present invention, and detailed implementation methods and operating procedures are provided. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following examples are usually carried out under normal conditions. Unless otherwise indicated, ratios and percentages are by weight.

[0057] Example 1

[0058] 1) Add 1 kg of alkaline silica sol with an average particle size of 12 nm, a solid content of 30%, and a pH of 11 and 500 g of a strongly acidic cation exchange resin (such as Zhengguang resin ZGC151) into a reaction vessel, heat to 50° C., and continue stirring for 1 hour;

[0059] 2) 20 g of methyltrimethoxysilane and 20 ml of 1 mol / L NaCl solution were added dropwise into the reaction vessel at a rate of 10 ml / h using a peristaltic pump. After the addition was completed, stirring was continued for 5 h;

[0060] 3) The reaction solution is cooled to 30°C, 200 g of anion exchange resin (such as ZGA351) is added, and stirring is continued. A pH meter is used to detect the dynamic change of the pH value of the system. When the pH value of the system is 7, stirring is stopped and filtering is performed. The filtered liquid is neutral methyltrimethoxysilane-modified silica sol (pH = 7).

[0061] Example 2

[0062] 1) Add 1 kg of alkaline silica sol with an average particle size of 20 nm, a solid content of 30%, and a pH of 10 and 400 g of a strongly acidic cation exchange resin (such as Zhengguang resin ZGC151) into a reaction vessel, heat to 45° C., and continue stirring for 1.5 h;

[0063] 2) A mixture of 10 g vinyltrimethoxysilane and 15 g methyltrimethoxysilane and 20 ml 1 mol / L KCl solution were added dropwise into the reaction vessel at a rate of 5 ml / h using a peristaltic pump. After the addition was completed, stirring was continued at 45° C. for 5 h;

[0064] 3) Cool down to 30°C, add 150g of anion exchange resin (such as Zhengguang resin ZGA351) into the reaction container, continue stirring, use a pH meter to detect the dynamic change of the pH value of the system, filter when the pH of the system is 7, and the filtered liquid is the neutral silica sol (pH = 7) modified by neutral vinyltrimethoxysilane and methyltrimethoxysilane.

[0065] Example 3

[0066] 1) Add 1 kg of alkaline silica sol with an average particle size of 30 nm, a solid content of 40%, and a pH of 10 and 600 g of a strongly acidic cation exchange resin (such as Zhengguang resin ZGC151) into a reaction vessel, heat to 55° C., and continue stirring for 1 hour;

[0067] 2) 15 g of aminopropyltrimethoxysilane and 12 g of methyltrimethoxysilane mixed solution and 30 ml of 1 mol / L NaCl solution were added dropwise into the reaction container at a rate of 5 ml / h using a peristaltic pump. After the addition was completed, stirring was continued at 55° C. for 6 h;

[0068] 3) The reaction solution is cooled to 15° C., 250 g of anion exchange resin (such as ZGA351) is added to the reaction container, and stirring is continued. A pH meter is used to detect the dynamic change of the pH value of the system. When the pH of the system is 5, the system is filtered. The filtered liquid is the acidic silica sol (pH=5) modified by acidic aminopropyltrimethoxysilane and methyltrimethoxysilane.

[0069] Example 4

[0070] 1) Add 1 kg of alkaline silica sol with an average particle size of 20 nm, a solid content of 20%, and a pH of 10 and 550 g of a strongly acidic cation exchange resin (such as Zhengguang resin ZGC151) into a reaction vessel, heat to 60° C., and continue stirring for 0.5 h;

[0071] 2) A mixture of 13 g of γ-glycidyloxypropyltrimethoxysilane and 10 g of methyltrimethoxysilane and 25 ml of 1 mol / L NaCl solution were added dropwise into the reaction container at a rate of 5 ml / h using a peristaltic pump. After the addition was completed, stirring was continued at 35° C. for 5 h;

[0072] 3) The reaction solution is cooled to 20° C., 200 g of anion exchange resin (such as Zhengguang resin ZGA351) is added to the reaction container, and stirring is continued. A pH meter is used to detect the dynamic change of the pH value of the system. When the pH of the system is 5, the system is filtered. The filtered liquid is the acidic silica sol (pH=5) modified by acidic γ-glycidyloxypropyltrimethoxysilane and methyltrimethoxysilane.

[0073] Comparative Example 1

[0074] The preparation method of the modified silica sol in this comparative example is different from that in Example 3 in that no NaCl aqueous solution is added. The specific steps are as follows:

[0075] 1) Add 1 kg of alkaline silica sol with an average particle size of 30 nm, a solid content of 40%, and a pH of 10 and 600 g of a strongly acidic cation exchange resin (such as Zhengguang resin ZGC151) into a reaction vessel, heat to 55° C., and continue stirring for 1 hour;

[0076] 2) 15 g of aminopropyltrimethoxysilane and 12 g of methyltrimethoxysilane were added dropwise to the reaction vessel at a rate of 5 ml / h using a peristaltic pump. After the addition was completed, stirring was continued at 55° C. for 6 h.

[0077] 3) The reaction solution is cooled to 15° C., 250 g of anion exchange resin (such as ZGA351) is added to the reaction container, and stirring is continued. A pH meter is used to detect the dynamic change of the pH value of the system. When the pH of the system is 5, the system is filtered. The filtered liquid is the acidic silica sol (pH=5) modified by acidic aminopropyltrimethoxysilane and methyltrimethoxysilane.

[0078] Comparative Example 2

[0079] The preparation method of the modified silica sol in this comparative example is different from that in Example 4 in that no NaCl aqueous solution is added. The specific steps are as follows:

[0080] 1) Add 1 kg of alkaline silica sol with an average particle size of 20 nm, a solid content of 20%, and a pH of 10 and 550 g of a strongly acidic cation exchange resin (such as Zhengguang resin ZGC151) into a reaction vessel, heat to 60° C., and continue stirring for 0.5 h;

[0081] 2) adding a mixture of 13 g of γ-glycidyloxypropyltrimethoxysilane and 10 g of methyltrimethoxysilane into the reaction vessel at a rate of 5 ml / h using a peristaltic pump. After the addition is complete, stirring is continued at 35° C. for 5 h;

[0082] 3) The reaction solution is cooled to 20° C., 200 g of anion exchange resin (such as Zhengguang resin ZGA351) is added to the reaction container, and stirring is continued. A pH meter is used to detect the dynamic change of the pH value of the system. When the pH of the system is 5, the system is filtered. The filtered liquid is the acidic silica sol (pH=5) modified by acidic γ-glycidyloxypropyltrimethoxysilane and methyltrimethoxysilane.

[0083] Comparative Example 3

[0084] The preparation method of the modified silica sol in this comparative example is different from that in Example 3 in that the alkaline silica sol itself is an alkaline system, and the silane reagent is directly added to react. The specific steps are as follows:

[0085] 1) Add 1 kg of alkaline silica sol with an average particle size of 30 nm, a solid content of 40%, and a pH of 10 into a reaction vessel, heat to 55° C., and continue stirring for 1 hour;

[0086] 2) 15 g of aminopropyltrimethoxysilane and 12 g of methyltrimethoxysilane were added dropwise to the reaction vessel at a rate of 5 ml / h using a peristaltic pump. After the addition was completed, stirring was continued at 55° C. for 6 h.

[0087] 3) The reaction liquid is cooled to 15° C. and filtered. The filtered liquid is the alkaline silica sol modified with alkaline aminopropyltrimethoxysilane and methyltrimethoxysilane.

[0088] After the reaction of the embodiment and the comparative example is completed, the color and state of the product are finally collected:

[0089]

[0090] From the results of the products collected in the examples and comparative examples, it can be seen that directly adding the silane reagent under alkaline conditions cannot bond the functional groups on the surface of the silica sol particles, and the silane will directly condense and gel under alkaline conditions to produce floccules.

[0091] Unmodified silica sol (the silica sol used in Example 3, an alkaline silica sol with an average particle size of 30 nm, a solid content of 40%, and a pH of 10), the modified silica sols of Examples 1-4, and the modified silica sols of Comparative Examples 1 and 2 were used to prepare water-based UV coatings, and these water-based UV coatings were coated on PVC substrates.

[0092] The unmodified silica sol or the modified silica sol is used to prepare a water-based UV coating, wherein the raw materials for preparing the water-based UV coating include the following components in parts by weight:

[0093]

[0094] The method for preparing the basic coating formulation comprises the following steps:

[0095] (1) Place the resin in a dispersion tank and stir with a mixer.

[0096] (2) slowly adding unmodified silica sol or modified silica sol, water, cosolvent, initiator, and wetting agent, and continuously stirring for 20 to 40 minutes to mix evenly;

[0097] (3) Slowly add thickener to adjust the viscosity of the coating according to different coating processes.

[0098] (4) Use a 200-mesh filter bag to filter and complete the preparation of water-based UV coating.

[0099] Application Example 1

[0100] This application example uses unmodified silica sol (alkaline silica sol with an average particle size of 30 nm, a solid content of 40%, and a pH of 10) to prepare a water-based UV coating.

[0101] Application Example 2

[0102] This application example uses the modified silica sol prepared in Example 1 to prepare a water-based UV coating.

[0103] Application Example 3

[0104] This application example uses the modified silica sol prepared in Example 2 to prepare a water-based UV coating.

[0105] Application Example 4

[0106] This application example uses the modified silica sol prepared in Example 3 to prepare a water-based UV coating.

[0107] Application Example 5

[0108] This application example uses the modified silica sol prepared in Example 4 to prepare a water-based UV coating.

[0109] Application Example 6

[0110] This application example uses the modified silica sol prepared in Comparative Example 1 to prepare a water-based UV coating.

[0111] Application Example 7

[0112] This application example uses the modified silica sol prepared in Comparative Example 2 to prepare a water-based UV coating.

[0113] Application Example 8

[0114] The above water-based UV coating is applied on the PVC substrate according to the following process:

[0115] (1) Providing a PVC substrate;

[0116] (2) Roll-coating the water-based UV coating of Application Example 1-7 on a PVC substrate;

[0117] (3) Bake at 60°C for 10 min, then use UV curing (medium pressure mercury lamp, 80-100 mW / cm 2 ,300~500mJ / cm 2 ).

[0118] The performance of the water-based UV coatings of the above application examples 1-7 on the PVC substrate was characterized. The hardness measurement standard is GB / T 6739-2022 paint and varnish pencil method to determine the paint film hardness, the adhesion measurement standard is GB / T 9286-2021 paint and varnish scratch test, and the iodine resistance standard is: internal inspection index (drop a drop of iodine on the surface of the test sample, cover it with a cover glass and let it stand for 10 minutes, then remove the cover glass and scrub it with 50% alcohol, and observe the depth of the residual yellow mark as the basis for judgment. The results are shown in Table 1 below.

[0119] Table 1

[0120]

[0121]

[0122] It can be seen from Table 1 that when the modified silica sols prepared in Examples 1-4 and Comparative Examples 1-2 are used in water-based UV coatings, the hardness, adhesion and iodine resistance of the water-based UV coatings can be significantly improved.

[0123] The preparation method of the modified silica sol of the present invention increases the bonding amount of silane on the surface of the silica sol particles, so that in the water-based UV coating system, the surface functional groups of the modified silica sol react chemically with the organic groups in the coating to form chemical bonds, thereby enhancing the bonding force between the coating and the substrate. This chemical bonding not only improves the adhesion of the coating, but also makes the coating denser, effectively prevents the intrusion of external substances such as moisture and oxygen, and prolongs the service life of the coating. At the same time, the addition of silica sol can also significantly improve the hardness and wear resistance of the coating, making it more durable.

[0124] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiment of the present invention can also be modified in various ways. That is, all simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.

Claims

1. A method for preparing a modified silica sol, characterized in that: The preparation method comprises the following steps: 1) mixing silica sol and cation exchange resin so that the pH of the mixed solution is 1 to 7; 2) adding a silane coupling agent and an aqueous solution of an inorganic salt to the mixed solution of step 1) to allow the silane coupling agent to bond to the surface of the silica sol; 3) adding anion exchange resin to the reaction solution of step 2) to make the pH value of the reaction system be 2-12, and filtering to obtain silica sol modified by silane coupling agent.

2. The method for preparing the modified silica sol according to claim 1, characterized in that: The silica sol has a pH of 8 to 12, a particle size of 5 to 100 nm, and / or The solid content of the silica sol is 5-40%, and / or The silane coupling agent is selected from alkoxysilanes containing alkyl substituents, alkoxysilanes containing unsaturated double bonds, alkoxysilanes containing epoxy groups, alkoxysilanes containing amino groups, or combinations thereof, and / or More preferably, the alkoxysilane containing an alkyl substituent is selected from methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, or a combination thereof, and / or More preferably, the alkoxysilane containing unsaturated double bonds is selected from vinyl trimethoxy silane, vinyl triethoxy silane, γ-methacryloxypropyl trimethoxy silane, or a combination thereof, and / or More preferably, the epoxy-containing alkoxysilane is selected from γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and / or More preferably, the amino-containing alkoxysilane is selected from aminopropyltrimethoxysilane, aminopropyltriethoxysilane, or a combination thereof.

3. The method for preparing the modified silica sol according to claim 1 or 2, characterized in that: The cation exchange resin is selected from styrene-divinylbenzene copolymers having sulfonic acid groups (-SO3H) or carboxylic acid groups (-COOH), and / or The inorganic salt is selected from sodium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, or a combination thereof, and / or The anion exchange resin is selected from styrene-divinylbenzene copolymers having quaternary ammonium groups [-N(CH3)3OH] or tertiary ammonium groups [-N(CH3)2].

4. The method for preparing the modified silica sol according to claim 1 or 2, characterized in that: Step 1) has one or more of the following characteristics: (i) the mass ratio of silica sol to dehydrated cation exchange resin is 1:0.1-0.9, preferably 0.3-0.8:1; (ii) stirring at 40-70°C for 0.5-2 h, more preferably at 45-60°C for 0.5-1.5 h.

5. The method for preparing the modified silica sol according to claim 1 or 2, characterized in that: Step 2) has one or more of the following characteristics: (i) The mass ratio of the silane coupling agent to the silica sol is 0.008 to 0.1:1, preferably 0.01 to 0.08:

1. (ii) the inorganic salt is used in an amount such that the mass ratio of the inorganic salt to the silica sol is 0.0001 to 0.01:1, preferably 0.0005 to 0.08:1, (iii) stirring continuously at 35-65° C. for 4-7 hours, more preferably, stirring continuously at 45-60° C. for 5-6 hours, (iv) the concentration of the aqueous solution of the inorganic salt is 0.2 to 5.0 mol / L, more preferably 0.5 to 1.5 mol / L, (v) The stirring rate is 10 to 200 rpm.

6. Use of the modified silica sol obtained by the preparation method according to any one of claims 1 to 5 in the preparation of water-based UV coatings, wherein the UV coatings are used for roller coating on PVC substrates.

7. A water-based UV coating, comprising a silica sol modified with a silane coupling agent obtained by the preparation method according to any one of claims 1 to 5.

8. The water-based UV coating according to claim 7, characterized in that: The raw materials used to prepare the water-based UV coating include the following components in parts by weight:

9. The water-based UV coating according to claim 8, characterized in that: The raw materials used to prepare the water-based UV coating include the following components in parts by weight:

10. The method for preparing the water-based UV coating according to claim 8, characterized in that: The preparation method comprises the following steps: (1) Place the water-based UV resin into a dispersion tank and stir with a mixer. (2) slowly adding modified silica sol, water, cosolvent, initiator, and wetting agent, and stirring continuously for 20 to 40 minutes to mix evenly; (3) Slowly add thickener to adjust the viscosity of the coating according to different coating processes. (4) Use a 200-mesh filter bag to filter and complete the preparation of water-based UV coating.

Citation Information

Patent Citations

  • Method for preparing electronic-grade silica sol

    CN101585541A

  • Silica sol and preparation method thereof

    CN104961134A

  • Preparation method of silica sol and application of silica sol in ceramic coating

    CN111017935A

  • Method for reducing viscosity of silica sol with high solid content

    CN114031085A

  • Method for improving water resistance of nano ceramic coating

    CN114292535A